0585 Understanding Excessive Daytime Sleepiness In Obstructive Sleep Apnea: The Effect Of Online Medical Education On Neurologists And Pulmonologists. (27th April 2018) - Finnegan, T; Hughes, S; Zee, P
Abstract: Introduction: Many clinicians do not consistently assess for, or adequately manage, excessive daytime sleepiness (EDS) in patients with obstructive sleep apnea (OSA). A study was undertaken to evaluate the effectiveness of an online educational in improving knowledge among neurologists and pulmonologists on the identification and management of EDS in OSA. Methods: The online continuing medical education (CME) activity consisted of a 30-minute video discussion between two faculty with expertise in sleep medicine. Educational effect was assessed by comparing neurologists'/pulmonologists' responses to four identical questions presented before and directly after exposure to education. A chi-square test identified differences between pre- and post-assessment responses. Cramer's V was used to calculate the effect size of the online education. Data from the participants in the educational intervention were collected between June 22, 2017, and August 11, 2017. Results: Participation in the CME intervention improved knowledge as indicated by a medium educational effect size among neurologists (n=42) and pulmonologists (n=112). The following areas showed significant ( P <0.05 for all) pre- to post-educational improvements for both groups: recognition of the dopamine and norepinephrine reuptake inhibitor being studied for EDS and knowledge of the minimum Epworth Sleepness Scale (ESS) score at OSA diagnosis associated with an increased likelihood of having residual sleepiness after CPAP treatment. A non-significant pre- to post-assessment improvement was seen in neurologists (73%) and pulmonologists (23%) regarding the relationship between apnea hypopnea index and obstructive hypopnea index on the level of sleepiness after CPAP therapy. 38% of neurologists and 34% of pulmonologists reported that participation in this educational activity improved confidence in identifying EDS at follow-up after treatment of the OSA. Conclusion: The results indicate that the CME-certified 30-minute video discussion was effective at improving knowledge regarding investigational therapeutics for and the identification of residual EDS in OSA. Future education efforts should continue to address investigational therapeutics and factors involved in the development of ESS in OSA. Support (If Any): The education and analysis was supported by an unrestricted educational grant from Jazz Pharmaceuticals.